Chlamydial infection in rheumatic diseases - S V Shubin; M M Urumova; E R Agababova; V R Martynova; N I Kolkova; E Y Morgunova; S A Sergienko; Y A Olyunin; S I Soldatova (Научно-практическая ревматология)
19 pts with reactive arthritis of urogenital origin, 3 with ankylosing spondylitis, 4 with undifferentiated spondyloarthritis, 4 with psoriatic arthritis and 8 with rheumatoid arthritis were included. Synovial tissue biopsies obtained during arthroscopy of 37 knee and 1 shoulder joints were examined by method of isolation in McCoy cell culture to reveal viable Chlamydia trachomatis. Chlamydia was isolated in 16 from 38 synovial tissue biopsies in all nosologic forms of arthritis except ankylosing spondylitis. In most cases Chlamydia isolation from synovial tissue coincided with presence of urogenital chlamydiosis